Families and Personal Networks An International Comparative Perspective (Palgrave Macmillan Studies in Family and Intimate Life, 2018)
This book critically assesses the main features of the modernization of family life and personal relationships by examining and comparing three European countries with different social and political pathways: Portugal, Switzerland and Lithuania. Drawing on national surveys of family trajectories and social networks, the contributors highlight personal and family relationships through the lens of network and life course perspectives as well as gender and generational perspectives. Providing innovative, comparative findings on families and personal networks through the use of diverse methodologies, this edited collection will be of interest to scholars, students and policymakers across a range of social science disciplines. .